1996
DOI: 10.1007/bf01273361
|View full text |Cite
|
Sign up to set email alerts
|

Pineal response after pyridoxine test in children

Abstract: To characterize the pineal response to pyridoxine, plasma melatonin was measured in one hundred and twenty children 3 hours after vitamin B6 administration. The children, aged between 1.5 and 8 years, were divided in four groups as follows: a) control day group, grouping 27 children sampled at 9:00 and at 12:00; b) control night group, grouping 29 children sampled at 21:00 and at 24:00; c) pyridoxine day group, grouping 30 children sampled at 9:00, then intravenously (i.v.) injected with 3 mg/kg of pyridoxine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…As folate is essential in the methylation step of converting N‐acetylserotonin to melatonin, folate deficiency decreases melatonin release in rats (Fournier, Ploye, Cottet‐Emard, Brun, & Claustrat, ). Moreover, vitamin B6 (pyridoxine) plays an important role in tryptophan decarboxylation and increases the release of melatonin by the pineal gland in children but not in adults (Munoz‐Hoyos et al, ; Luboshitzky et al, ).…”
Section: Biosynthesismentioning
confidence: 99%
“…As folate is essential in the methylation step of converting N‐acetylserotonin to melatonin, folate deficiency decreases melatonin release in rats (Fournier, Ploye, Cottet‐Emard, Brun, & Claustrat, ). Moreover, vitamin B6 (pyridoxine) plays an important role in tryptophan decarboxylation and increases the release of melatonin by the pineal gland in children but not in adults (Munoz‐Hoyos et al, ; Luboshitzky et al, ).…”
Section: Biosynthesismentioning
confidence: 99%
“…Nocturnal melatonin levels in the blood, however, doubled in over 100 small children between the ages of 18 months and 8 years when pyridoxine was administered at night intravenously at doses of 3 mg/kg (78). Any possible deficiency of pyridoxine in these hospitalized children was not reported.…”
Section: Availability Of Nutrientsmentioning
confidence: 99%
“…11 Vitamin B6 acts as a coenzyme for the decarboxylation of tryptophan and leads to the melatonin synthesis in children at pre-pubertal ages. 12 Some studies have reported that Vitamin B6 does not affect the secretion of melatonin in adults. 13 However, it is observed that injections of vitamin B6 strengthen the biosynthesis of melatonin.…”
Section: Introductionmentioning
confidence: 99%
“…Some factors affect the synthesis of melatonin including the availability of tryptophan, folate status, and vitamin B6 11 . Vitamin B6 acts as a coenzyme for the decarboxylation of tryptophan and leads to the melatonin synthesis in children at pre‐pubertal ages 12 . Some studies have reported that Vitamin B6 does not affect the secretion of melatonin in adults 13 .…”
Section: Introductionmentioning
confidence: 99%